Cell cycle and cleavage events during in vitro cultivation of bloodstream forms of Trypanosoma lewisi, a zoonotic pathogen. Issue 5 (4th March 2019) - Zhang, Xuan; Li, Su-Jin; Li, Ziyin; He, Cynthia Y.; Hide, Geoff; Lai, De-Hua; Lun, Zhao-Rong
ABSTRACT: Trypanosoma ( Herpetosoma ) lewisi is a globally distributed rat trypanosome, currently considered as a zoonotic pathogen; however, a detailed understanding of the morphological events occurring during the cell cycle is lacking. This study aimed to investigate the cell cycle morphology and cleavage events of Trypanosoma lewisi ( T. lewisi ) during in vitro cultivation. By establishing in vitro cultivation of T. lewisi at 37°C, various cell morphologies and stages could be observed. We have provided a quantitative analysis of the morphological events during T. lewisi proliferation. We confirmed a generation time of 12.14 ± 0.79 hours, which is similar to that in vivo (12.21 ± 0.14 hours). We also found that there are two distinct cell cycles, with a two-way transformation connection in the developmental status of this parasite, which was contrasted with the previous model of multiple division patterns seen in T. lewisi . We quantified the timing of cell cycle phases (G1n, 0.56 U; Sn, 0.14 U; G2n, 0.16 U; M, 0.06 U; C, 0.08 U; G1k, 0.65 U; Sk, 0.10 U; G2k, 0.17 U; D, 0.03 U; A, 0.05 U) and their morphological characteristics, particularly with respect to the position of kinetoplast(s) and nucleus/nuclei. Interestingly, we found that both nuclear synthesis initiation and segregation in T. lewisi occurred prior to kinetoplast, different to the order of replication found in Trypanosoma brucei and Trypanosoma cruzi, implicating a distinct cell cycle control mechanism in T. lewisi . We characterized the morphological events during the T. lewisi cell cycle and presented evidence to support the existence of two distinct cell cycles with two-way transformation between them. These results provide insights into the differentiation and evolution of this parasite and its related species.